Neuroanatomy of Gryposuchus neogaeus (Crocodylia, Gavialoidea): a first integral description of the braincase and endocranial morphological variation in extinct and extant gavialoids - Bona, Paula (2017)
Morphological studies of the braincase and cranial endocast of fossil crocodylians, especially gavialids, are scarce. Here, we present a detailed description of the neuroanatomy of Gryposuchus neogaeus from the Miocene of Argentina, based on CT scans. The cranial endocast is sub-horizontal and the angle formed between the mid-brain and the hind-brain is poorly marked. When compared with Gavialis gangeticus, the mid-brain of G. neogaeus is relatively shorter, although the distribution of cranial nerves is similar. In the floor of the endocranial cavity, posterior to the dorsum sellae, there is a median foramen that leads into a canal that runs anteroventrally through the basisphenoid to penetrate the posterior wall of the pituitary fossa (open foramen for the basilar artery?). The same structure is present in G. gangeticus, but is absent in other living crocodylians, suggesting a potential synapomorphy of Gavialoidea. The pneumaticity of the skull roof and the lateral branches of the pharyngotympanic system in G. neogaeus are markedly reduced when compared with the extant species. Comparisons with the living Gavialis indicate that the pattern of braincase morphology of Gavialidae was present in the Miocene; however, the internal morphology, including brain shape, pneumaticity of the skull roof and basicranium, is different in the two species. This work is the first step to understand the variation of the neuroanatomy in this group of archosaurs and its palaeobiological implication.